Uncovering Nanoclusters in Amorphous AlN: An Ab Initio Study - Durandurdu, Murat (Wiley, 2014)
Amorphous AlN (a-AlN) is modeled by melt-and-quench technique using ab initio molecular dynamic simulations. For the first time, three-dimensional hexagonal-like nanoclusters embedded in amorphous matrix are proposed for a-AlN. The model is chemically ordered and dominantly fourfold coordinated, but its short-range order is partially different from the crystalline morphology due to the nanoclusters. The model is semiconducting with a theoretical band gap of 1.7eV.
Durandurdu, Murat/0000-0001-5636-3183;